Bibliometric analysis of cognitive dysfunction after traumatic brain injury - Hu, Jihua; Zhu, Ruiting; Zhang, Xin; Zhang, Yuchen; Liu, Jixin; Wang, Wenyang; Li, Chiyin; Yang, Tong; Zhang, Ming; Niu, Xuan (Frontiers in Neuroscience, 2025)
BackgroundCognitive dysfunction after traumatic brain injury (TBI) significantly reduces quality of life and imposes a heavy burden on society. A detailed examination of research trends of cognitive dysfunction following TBI has not yet been conducted. This study aimed to examine the bibliometric analysis of cognitive dysfunction after traumatic brain injury over the past 20 years.MethodsLiterature on bibliometric analysis was retrieved from the Web of Science Core Collection (WoSCC) and Science Citation Index Expanded (SCI-E) from 2004 to 2023. The type of literature and the language were refined. A total of 1,902 articles were used for bibliometric analysis, including 1,543 (81.1%) original articles and 359 (18.9%) review articles. Data were retrieved on June 5, 2024.ResultsThe publication volume of articles was increasing year by year, with articles published in 537 journals. The Journal of Neurotrauma, with 130 articles, was the most productive and influential journal. The University of California System led in the number of articles published. There were 9,002 authors from 62 countries/regions. The USA and China were the top-ranked countries by article count. Pandharipande PP authored the highly cited article. Pick CG, as the author with the highest h-index. The top three of author keywords were traumatic brain injury, cognitive impairment, and mild traumatic brain injury. The topics of cognitive dysfunction after TBI were ferroptosis, cognitive decline, spinal cord injury, and prognosis.ConclusionOur findings provide valuable insights into cognitive dysfunction following TBI and highlight emerging trends for future research.